Социофонетическая вариативность английского языка в ЮАР - Устинович, Е.А. (Культура народов Причерноморья, 2004)
The article deals with the correspondence between the social structure of the South-African society and the variety in spoken English in South Africa. It is argued that there are four major types of pronunciation, which are briefly described in the article. The conclusion is drawn that due to the recent social changes in South Africa, phonetic restandartization of the com-monly accepted national English is to be expected.